Increment of placental Caspase 3 expression in preeclampsia and its effect on birth weight and blood pressure - Teguh, Mintareja (Indonesian Journal of Obstetrics and Gynecology, 2010)
Objective: To determine the placental apoptosis process in preeclampsia. Methods: This study was an observational analytical study using cross sectional design. This study was performed at Dr. Hasan Sadikin Hospital, during April to June 2008. Immunohistochemical analysis was used to examine the placental expression of kaspase 3. Results: Placental expression kaspase 3 was significantly higher in preeclampsia group (21,9%) than in the normal pregnancies (0) with p=0,006. There was significantly correlation between placental kaspase 3 with birth weight in preeclampsia on the otherhand, there was no significant difference of placental expression kaspase 3 with birth weight in normal pregnancies. There was no significant difference of placental expression kaspase 3 with motherâs blood pressure in the two group. Conclusion: there is a significant increase of placental expression of kaspase 3 in preeclampsias. [Indones J Obstet Gynecol 2010; 34-1:3-6] Keywords: caspase 3, preeclampsia, apoptosis.